Professional life quality as correlate to job satisfaction of public elementary teachers: Basis for mental health fatigue solace program - Anthony S. Gonzales; Dennis G. Caballes (Northern Negros State College of Science and Technology (NONESCOST), 2023)
Teachers' professional life quality and job satisfaction are essential factors in the success of their careers as prime movers of learning. This study explored the relationship between professional life quality and job satisfaction of public elementary teachers through a descriptive-correlational research design. Pearson Product Moment correlation was used to assess the relationship between variables, while multiple regression analysis was also utilized to bolster the link between professional life quality and the job satisfaction of teachers. The findings of the study revealed that indebtedness, health and safety, financial literacy, and family responsibilities subscales sometimes and fairly affect their professional life quality. Teachers have a very high level of satisfaction on community linkages, high level of satisfaction on job responsibilities, while security and working environment have fair levels of job satisfaction. Furthermore, professional life quality has a significant relationship on the job satisfaction of teachers. The recommendations provide information to the school leaders and the human resource department, allowing them to focus on key aspects that could improve the satisfaction, welfare, and well-being of their employees. The findings of this study can be utilized for the development of interventions and policies that can enhance the quality of life and job satisfaction of teachers, leading to a more engaged and productive workforce in the education sector.